PENGARUH TOTAL QUALITY MANAGEMENT DAN JUST IN TIME TERHADAP KINERJA OPERASIONAL KARYAWAN EMP MALACCA STRAIT PSC - Bunga Nabilla Ghazani; Imam Wibowo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to analyze the effect of total quality management on cost efficiency at EMP Malacca Strait, the influence of just in time on operational performance at EMP Malacca Strait and total quality management and just in simultaneously on operational performance at EMP Malacca Strait. The number of samples in this study were 78 respondents. The analysis technique uses simple regression analysis and multiple regression. The results showed that total quality management and just in time simultaneously had a significant effect on operational performance because total quality management was maintained in terms of teamwork. According to the employees doing work with full responsibility and supported by the standard of time used to support control of production costs. Total quality management has a positive effect on operational performance. This shows that total quality management that are maintained in terms of teamwork according to the employees doing work with full responsibility can improve operational performance. Just in time has a positive effect on operational performance. This shows that the standard of time used to support control of production costs can significantly improve operational performance.